Assessment of simultaneous addition of sucrose and xanthan effects on the thermal, pasting, and rheological behavior of corn starch. Issue 3 (17th December 2019) - Zolelmein, Aida; Movahhed, Sara; Azizi, Mohammad Hossein; Ahmadi Chenarbon, Hossein
Abstract: Thermal, pasting, and rheological properties of starch‐based systems are the key characteristics for its processing. This study aimed to investigate the main and interactive effects of sucrose and xanthan on the thermal, pasting, and rheological behavior of corn starch. A central composite design (CCD) was used to evaluate the effect of simultaneous addition of sucrose and xanthan on some processing properties of starch‐based systems. The results showed that besides the xanthan and sucrose effects ( p  < .001), the interactions played a significant role in all considered properties of corn starch except the flow behavior index ( p  < .05). Adding xanthan and sucrose increased the transition temperatures and the enthalpy change (Δ H ) of the starch gelatinization, while they increased all pasting properties except setback viscosity. Statistical analysis results revealed the synergistic effects due to adding xanthan and sucrose on the thermal and pasting properties of starch. These were ascribed to the first‐ and second‐order interaction effects ( p  < .05). Regression models proposed for prediction of all considered properties of the starch‐based mixtures in the range of selected factors ( R 2 > 0.88). The Fourier‐transform infrared (FTIR) spectra revealed an increase in hydrogen bonding by increasing xanthan and sucrose. Since the formation of hydrogen bonds between mixture components could be affected the considered properties of the starch pastes. Practical applications: Starch‐based foods are the most frequently consumed kind of foods in the developing countries, which provide a great deal of energy, and nutrients in a healthy diet. Therefore, the production of these kinds of food products is of great importance. The gelatinization, pasting, and rheological properties of starch‐based foods are imperative aspects in its processing. These properties show differences according to the presence of other ingredients such as hydrocolloids and sweeteners. Since the addition of xanthan as hydrocolloid and sugar as a common sweetener in starch‐based foods, affect optimal processing condition. Knowing the effects of the hydrocolloid and sweetener addition on thermal, pasting, and rheological properties of starch systems, help to improve the process and finding optimal process conditions for the production of sauces, baby foods, bread, confectionery, etc.